Aplicação de técnicas de agricultura de precisão em áreas do cultivo do fumo na agricultura familiar - Vidal, Leonice Raquel (2016)
Tobacco growing is one of family farming s main economic activities in the central region of the Rio Grande do Sul state. This paper aims to administer precision agriculture techniques in tobacco growing area of family farming, using tools with lesser degree of complexity, sophistication and cost in order to evaluate the variability and quantify the productivity of the soil. To achieve this, a crop in the municipality of Agudo (RS) characterized by the presence of family farming and the tobacco growing as the basis of rural municipal economy was chosen as the study area. The methodological procedures were based on the vectorization of a crop (0.4-hectare), which was divided into two areas: CAP1 area and SAP1 area. In the CAP1 area, high precision techniques like soil analysis and variable rate correction were performed and, after the analysis of these data, the correspondent agricultural inputs needed were to the experiment area. The SAP1 area complied to the interventions of the family farmers and the agricultural technician of the tobacco company. The experiment was carried out during the years 2014 (base year without intervention) and 2015 (year that the precision agriculture techniques were applied), the obtained data took into account the two areas, in order to establish productivity correlation in each area, taking in consideration the amount of leaves per plant, the width and length of the sheet, the size of the plant and the total weight of each tobacco plant. Amongst the obtained results, it can be highlighted the efficiency of the precision agriculture techniques in tobacco plants, increased soil fertility in the CAP1 area and increased productivity. In the CAP1 area, productivity rose 91,9%, while in SAP1 area, productivity rose 50,7% in comparison between 2014 and 2015. Comparing both areas during the year in which the techniques were applied, CAP1 was 35,24% more productive than SAP1, showing that it is viable to apply the aforementioned techniques and its efficacy in decision making for family farming activities.